Customary Deprivation: Perceptions of Legatee in Igbo land and Female Property Crimes amongst Enugu Urban Inhabitants - Aroh, Amadi; Eze, Obinna J. (International Journal of Criminology and Sociology, 2024)
This study aims to garner perceptions of Enugu inhabitants on the customary practice of property transfer to inheritors and its nexus to female property crimes (FPCs). Inheritance is an age-old practice which tends to favour male folks. Women have often been relegated to the kitchen. This practice is embedded in most African cultures where the birth of a male is valued over the birth of a female child. Denial of female rights of inheritance, denial of ownership of landed property, and female marginalization in almost all social institutions seem to stem from patriarchy which in turn tend to predispose women to property crimes. This study anchored on Relative Deprivation theory. Mixed method approach was adopted. Sampling of participant was based on multi-stage sampling procedure and purposive sampling. The sample size is 1015 for the quantitative part of the study and nine key informants for the qualitative aspect. This study found that the customary practice of legatee in Igbo land is embedded in patriarchy and this holds adverse economic effects for women, culminating in FPCs which involve women of youthful age who are mostly in full blown exposure of the existing privileges and cover offered to women in patriarchal societies especially when married. This study concludes that patriarchy understood as domination of vital social and political positions by men and exclusion of women from inheriting family lands and properties is implicit to FPCs.